Surface Modification of Erythrocytes with Lipid Anchors: Structure–Activity Relationship for Optimal Membrane Incorporation, in vivo Retention, and Immunocompatibility. Issue 8 (19th July 2022) - Gaikwad, Hanmant; Wang, Guankui; Li, Yue; Bourne, David; Simberg, Dmitri
Abstract : Red blood cells (RBCs) are natural carriers for sustained drug delivery, imaging, and in vivo sensing. One of the popular approaches to functionalize RBCs is through lipophilic anchors, but the structural requirements for anchor stability and in vivo longevity remain to be investigated. Using fluorescent lipids with the same cyanine 3 (Cy3) headgroup but different lipid chain and linker, the labeling efficiency of RBCs and in vivo stability are investigated. Short‐chain derivatives exhibited better insertion efficiency, and mouse RBCs are better labeled than human RBCs. Short‐chain derivatives demonstrate low retention in vivo. Derivatives with ester bonds are especially unstable, due to removal and degradation. On the other hand, long‐chain, covalently linked derivatives show remarkably long retention and stability (over 80 days half life in the membrane). The clearance organs are liver and spleen with evidence of lipid transfer to the liver sinusoidal endothelium. Notably, RBCs modified with PEGylated lipid show decreased macrophage uptake. Some of the derivatives promote binding of antibodies in human plasma and mouse sera and modest increase in complement deposition and hemolysis, but these do not correlate with in vivo stability of RBCs. Ultra‐stable anchors can enable functionalization of RBCs for drug delivery, imaging, and sensing. Abstract : There is a great interest in modifications of erythrocytes with lipids for biomedical applications. A library of fluorescent lipids is screened for stable incorporation into human and mouse erythrocytes. The modified erythrocytes are then injected in mice and tested for the stability of the lipid and the circulation properties. The structural requirements to decrease the immune recognition are also investigated.